2018
DOI: 10.1186/s12864-018-4617-x
|View full text |Cite
|
Sign up to set email alerts
|

Variance explained by whole genome sequence variants in coding and regulatory genome annotations for six dairy traits

Abstract: BackgroundThere are an exceedingly large number of sequence variants discovered through whole genome sequencing in most populations, including cattle. Deciphering which of these affect complex traits is a major challenge. In this study we hypothesize that variants in some functional classes, such as splice site regions, coding regions, DNA methylated regions and long noncoding RNA will explain more variance in complex traits than others. Two variance component approaches were used to test this hypothesis – the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 52 publications
(96 reference statements)
6
20
0
Order By: Relevance
“…These results are in agreement with the report by Koufariotis et al [40] that the intron and intergenic variants explained the lowest proportion of the genetic variance per SNP basis for milk and fertility traits in dairy cattle, which is likely due to much larger number of DNA variants in the class and majority of them have small or zero effects on the traits. Notable, 3'UTR and synonymous variants captured a greater amount of additive genetic variance per sequence variant for all the traits, which are in line with the results reported by Koufariotis et al [41] for milk production traits in dairy cattle. These results indicate a greater role of 3'UTR variants in affecting the complex traits, which is also supported by previous studies that have shown that microRNAs interact with target sites in 3'UTR of mRNA to regulate their gene expressions [42,43].…”
Section: Snp Effects Related To Snp Functional Classessupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in agreement with the report by Koufariotis et al [40] that the intron and intergenic variants explained the lowest proportion of the genetic variance per SNP basis for milk and fertility traits in dairy cattle, which is likely due to much larger number of DNA variants in the class and majority of them have small or zero effects on the traits. Notable, 3'UTR and synonymous variants captured a greater amount of additive genetic variance per sequence variant for all the traits, which are in line with the results reported by Koufariotis et al [41] for milk production traits in dairy cattle. These results indicate a greater role of 3'UTR variants in affecting the complex traits, which is also supported by previous studies that have shown that microRNAs interact with target sites in 3'UTR of mRNA to regulate their gene expressions [42,43].…”
Section: Snp Effects Related To Snp Functional Classessupporting
confidence: 90%
“…1. At the suggestive significant level of P-value < 0.005, 41,248,46,455,44,746, and 47,923 SNPs (i.e. sequence variants) were found to be associated with RFI, DMI, ADG, and MWT, respectively (Table 2).…”
Section: Top Significant Snps Associated With Rfi and Its Component Tmentioning
confidence: 99%
“…Variants annotated as coding related, of which the majority of variants are missense and synonymous (SI Appendix, Table S1), had relatively low ranking of genetic importance to complex traits (Figure 3). It seems a surprising result, but Koufariotis et al also reported similar observations in cattle (50). Perhaps coding variants that influence phenotype are subject to purifying selection and hence have low heterozygosity and hence low contribution to variance.…”
Section: Discussionmentioning
confidence: 90%
“…The variant annotation sets of non-coding related and splice sites ranked relatively high for their contribution to trait variation ( Figure 3). Previously, variants annotated as splice sites had a high ranking of genetic importance to cattle complex traits (50). The majority of the variants from the non-coding related set are 'non_coding_transcript_exon_variant' (SI Appendix, Table S1) which is 'a sequence variant that changes non-coding exon sequence in a non-coding transcript' according to VEP (28).…”
Section: Discussionmentioning
confidence: 99%
“…Lactation performance is a complex quantitative trait affected by several crucial factors including genetic background, nutrition, and environment (Carcangiu et al, 2018). Over the past decade, the influences of genetic variations on milk performance in animals have been extensively studied (Koufariotis et al, 2018). Recently an increasing number of studies have demonstrated that nutritional or environmental changes contribute to changes in inheritable epigenetic modifications, such as DNA methylation (Lan et al, 2013a;Chavatte-Palmer et al, 2018;Kwan et al, 2018;Yuan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%